Synergistic risks of ambient air particulate matter and ozone exposure on low birth weight: An 11-year longitudinal Chinese maternity cohort study - Haitong Zhe Sun; Han Chen; Yijia Tian; Zekun Wang; Juan Zhou; Lina Zhang; Jing Fang; Juan Gao; Kim Robin van Daalen; Lynette P. Shek; Wei Jie Seow; Yuming Guo; et al. (Environment International)
Observational epidemiological studies have demonstrated that maternal exposure to air pollution increases the risk of adverse pregnancy outcomes. However, interactions among multiple environmental exposures remain underexplored. In this study, we performed an epidemiological analysis on 147,979 pregnant women recruited from nine provinces in southeastern China between 2013 and 2023, focusing on the risk of low birth weight (LBW). We found that the critical exposure windows for PM2.5 and ozone (O3) extend from six months prior to conception through the end of second trimester, with hazard ratio of HR = 1.152 (95 % confidence interval [CI]: 1.128–1.177) per 10-μg/m3 incremental PM2.5 exposure and HR = 1.028 (95 % CI: 1.024–1.031) per 10-ppb increase in O3. Our estimates indicate that in 2021, approximately 47,500 (95 % uncertainty interval [UI]: 41,200–53,600) live-born LBW infants nationwide in China could be attributed to ambient air pollution, declining from 79,800 (95 % UI: 71,700–87,900) in 2002. We observed statistically significant synergistic risk effects, neglecting which could lead to an underestimation of 11,600 (95 % UI: 9,300–13,900) LBW cases. Although air pollution-associated LBW burden is decreasing, the rapidly rising LBW prevalence remains a significant public health concern, particularly as China is implementing the “three-child policy”. Therefore, our study offers precisely quantified, evidence-based policy guidance for safeguarding reproductive health.